Determination of Company Performance: Analysis of Motivation, Leadership, Organizational Commitment and Employee Engagement - Rahadian Yudistira, Yusuf; Al Faruq Abdullah, Muhammad (Siber Nusantara Research & Yayasan Sinergi Inovasi Bersama (SIBER), 2024)
The article on determining company performance: Analysis of motivation, leadership, organizational commitment and employee engagement is a scientific literature article within the scope of human resource management science. The aim of this research is to build a hypothesis regarding the influence between variables which can later be used for further research within the scope of human resource management. The research method used is descriptive qualitative. Data was obtained from previous research that is relevant to this research and sourced from academic online media such as Publish or Perish, Google Scholar, digital reference books and the journal Sinta. The results of this article are: 1) Motivation influences company performance; 2) Leadership influences company performance; 3) Organizational Commitment influences Company Performance; and 4) Employee Engagement influences Company Performance.